PROGRAMA INNOVADOR PARA EVALUAR USO Y PREFERENCIA DE HÁBITAT - Javier Montenegro; Alberto Acosta (Universitas Scientiarum)
The species habitat preference is an important topic in biology, ecology, evolution, and management andconservation of biodiversity, since it allows us to determine the resources and conditions required by species forsurvival, reproduction and persistence through time. This topic is high priority due to the rapid climatic changesthat, according to model predictions, will directly or indirectly affect the resources, conditions and therefore itshabitat, modifying its abundance, spatial distribution, and local probability of extinction. At the moment thistopic is difficult to approach, because the existing literature is disperse, there are theoretical contradictions, andmathematical methods to infer preference are repetitive, and have not been ranked. Considering these difficulties,HaviStat© has been created. This program can perform the majority of mathematical, statistical, and graphicalprocedures required to infer habitat use, selection, preference or resources (18 indices and 2 confidence intervals),and niche amplitude for any species (4 indices and 2 confidence intervals). The program was made on VisualBasic® language on the Microsoft Office Excel® platform. It is the result of an exhaustive literature review,where the most relevant index were selected and compiled. Complementary literature will help researchers to setup experimental designs, and to know the importance of the results; also, it will bring basic tools to understandhow the index work and when they must be applied.